PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS ANDROID DATABASE KOMPONEN LISTRIK - Arif Harun Nadzar; Edy Supriyadi (Jurnal Edukasi Elektro, 2020)
ABSTRACT:The purpose of this study were: (1) to develop Android-based learning media to assist the learning process of class X students of Electrical Power Installation Engineering also called TITL, (2) to determine the feasibility of learning media based on material and media aspects, (3) to determine the user's response to learning media. This is a research and development with the ADDIE model. The media feasibility test uses expert judgment. This research was implemented in vocational school at SMK N 1 Pundong. The research subjects were 38 students of class X TITL. The assessment instrument uses a questionnaire with a Likert scale of four choices. The data analysis technique used descriptive analysis. The results of this research and development were: (1) the product in the form of an android application "Electrical Component Database" as a learning media at SMK N 1 Pundong, (2) the results of the product feasibility test by material experts obtained a score of 64 out of 72 and categorised as "Very good", The results of the product feasibility test by media experts obtained a score of 71 out of 88 and categorised as " Good ", (3) students' responses to the product obtained a mean score of 115.2 out of 140 and categorised as " Very good ".ABSTRAK:Tujuan penelitian ini adalah: (1) mengembangkan media pembelajaran berbasis android untuk membantu proses belajar siswa kelas X Teknik Instalasi Tenaga Listrik (TITL), (2) mengetahui kelayakan media pembelajaran berdasarkan aspek materi dan media, (3) mengetahui respons pengguna terhadap media pembelajaran. Penelitian ini merupakan research and development dengan model ADDIE . Uji kelayakan media menggunakan expert judgment. Penelitian ini dilaksanakan di SMK N 1 Pundong. Subjek penelitian sebanyak 38 siswa kelas X TITL. Instrumen penilaian menggunakan kuisioner dengan skala likert empat pilihan. Teknik analisis data menggunakan analisis deskriptif. Hasil penelitian dan pengembangan ini adalah: (1) produk berupa aplikasi android “Database Komponen Listrik” sebagai media pembelajaran di SMK N 1 Pundong, (2) hasil uji kelayakan produk oleh ahli materi diperoleh skor 64 dari skor maksimal 72 dengan kategori “Sangat Layak”, hasil uji kelayakan produk oleh ahli media diperoleh skor 71 dari skor maksimal 88 dengan kategori “Layak”, (3) respons siswa terhadap produk diperoleh skor rerata 115,2 dari skor maksimal 140 dengan kategori “Sangat Layak”.